Design and Development of Welding Data Processing System. Issue 1 (August 2021) - Wang, Laizhen; Long, Bin; Duan, Ruibin; Wang, Kekuan; Lv, Li
Abstract: Through database technology, welding data management technology and automatic analysis storage technology, a management system for welding process monitoring is designed and developed in C# environment, which realizes the integrated automatic management of real-time analysis, processing, storage and uploading of welding data; at the same time, it can make statistical analysis of historical data and generate reports. In addition, the system also has scalability, which provides technical support for the construction of "intelligent pipeline and smart pipe network" in the future.